Pembaharuan Undang-Undang Nomor 40 tahun 2007 Tentang Perseroan Terbatas Dalam Rangka Memaksimalkan Program Tanggung Jawab Sosial Lingkungan - Hamzah, Rosyidi; Adinda, Fadhel Arjuna; Admiral, Admiral; Taupik, Muhammad; Amin, Muhammad Nur (Lex Librum : Jurnal Ilmu Hukum, 2024)
Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies establishes social and environmental responsibilities for companies operating in or related to natural resources. Companies based on information and technology must also be accompanied by changes in legal norms, especially in the field of implementing environmental social responsibility. According to Law Number 40 of 2007 concerning Limited Liability Companies, only companies whose business activities are related to natural resources or businesses that impact the environment are subject to environmental social responsibility, while IT startups and digital businesses do not disturb natural resources and do not affect the environment. Changes in society are indeed followed by changes in legal norms. The older a law gets, the more weaknesses and shortcomings it will have. Changes in norms governing environmental social responsibility must be adjusted to the current business climate. Environmental Social Responsibility should also be mandated for companies operating in the digital business sector. To maximize environmental social responsibility for large companies operating in the digital business sector, it must be supported by adequate legal norms.